Literature Review: Tele-nursing education to increase adherence fluid restriction in patients with End Stage Renal Disease undergoing hemodialysis - Ana Khumaeroh; imam subiyanto; Teti Hayati (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Background: Patients with End Satge Renal Disease (ESRD) should undergoing  hemodialysis therapy for excess fluid, solutes and toxins. To achieve hemodialysis success, there are four factors including diet, drug use, fluid intake restriction and the presence of hemodialysis. Limiting fluid intake is important for hemodialysis patients because excess fluid can cause interdialytic weight gain (IDGW) which will have an impact on cardiovascular complications such as congestive heart failure, pulmonary edema and death. However, meeting fluid requirements becomes a problem for HD patients and it is estimated that 30-70% of patients fail to meet fluid requirements. One of the interventions to improve fluid readiness is to increase patient knowledge about fluids.Purpose: This literature review aims to determine and review the results of research on the effectiveness of telenursing on fluid adherence in hemodialysis patients. Methods: This research is a literature review with a narrative method to explore research results by searching several database including ebcohost, scopus, proquest and sciendirect with keyword: hemodialysis, telenursing, tele education, nurse led telephone follow ups, tele-health, face to face education, education program, education based on behavior, adherence to fluid intake restriction and compliance to fluid intake restriction. The search for these journals is limited in the period from 2012 to 2021, with filters for full text, journals, English language and journals according to the topic which is then carried out critically in each journal to produce research conclusions.Results: It was found that telenursing was effective in adjusting use in hemodialysis patients, reducing depression, anxiety and stress in hemodialysis patients. In addition, the provision of direct or face-to-face education programs can also increase knowledge and adherence to direct contact with fluids, but in the results it is recommended to follow up with telephone or use telenursing to improve care and can reduce self-care of HD patients remotely.Conclusion: Based on the results based on a systematic basis, it was found that the use of telenursing education can increase adherence to knowledge and fluid compliance of hemodialysis patients and can reduce depression, anxiety and stress.Keyword: Tele nursing education, ESRD, Fluid Restriction, Hemodialysis